PEMANFAATAN TANAMAN REFUGIA MENGENDALIKAN HAMA PADI (Oryza nivara L) DI SOPORARU TAPANULI UTARA - Ameilia Zuliyanti Siregar; Sampe Lesnida (Universitas 17 Agustus 1945 Samarinda, 2021)
The refugia plant is one of the flowers that can be used as a shelter for natural enemies and as a feed sources for insects. The purpose of this study was to compare the use of refugia and without refugia plants in controlling environmentally friendly red rice pests in Soporaru Hamlet, Sigotom JuluVilalge, Pangaribuan District, North of Tapanuli Regency, North of Sumatra Province. This study uses a purposive sampling method with 3 types of traps, namely: yellow traps, fall traps and net traps. The samples was identified in the Plant Disease Laboratory, Faculty of Agriculture, University of North Sumatra in July 2020 until February 2021. The results showed that 8 orders of refugia were caught on land using refugia, 23 families, and 1,952 individuals, while on land without refugia there were 8 orders, 22 families and 1,807 individuals. On land using refugia (r) compared to land without refugia (k) it is known that the Species Richness Index (R) (Rr=2.9 and Rk=2.8), Diversity Index (H) (Hr=2.67 and Hk= 2.19), and Evenness Index (E) (Er=0.85 and Ek=0.71). Function status identified on land using refugia and without refugia as many as 5 species, namely herbivores, pollinators, predators, parasitoids and scavengers.